The green fairy book - Lang, Andrew, 1844-1912; Ford, H. J. (Henry Justice), 1860-1941; Lang, Andrew, 1844-1912; Spottiswoode & Co.; Longmans, Green, and Co. (London : Longmans, Green, 1892)
Fairy tales from the folklore of France, Germany, Scotland, England, Italy, and one from China.
The blue bird -- The half-chick -- The story of Caliph Stork -- The enchanted watch -- Rosanella -- Sylvain and Jocosa -- Fairy gifts -- Prince Narcissus and the Princess Potentilla -- Prince Featherhead and the Princess Celandine -- The three little pigs -- Heart of ice -- The enchanted ring -- The snuff-box -- The golden blackbird -- The little soldier -- The magic swan -- The dirty shepherdess -- The enchanted snake -- The biter bit -- King Kojata -- Prince Fickle and fair Helena -- Puddocky -- The story of Hok Lee and the dwarfs -- The story of the three bears -- Prince Vivien and the Princess Placida -- Little One-eye, Little Two-eyes, and Little Three-eyes -- Jorinde and Joringel -- Allerleirauh : or The many furred creature -- The twelve huntsmen -- Spindle, shuttle, and needle -- The crystal coffin -- The three snake-leaves -- The riddle -- Jack my hedgehog -- The golden lads -- The white snake -- The story of a clever tailor -- The golden mermaid -- The war of the wolf and the fox -- The story of the fisherman and his wife -- The three musicians -- The three dogs.
Mode of access: Internet.
Keywords: Children's stories; Publishers' advertisements -- 1892.; Fantasy literature -- 1892.; Fairy tales -- 1892.; Children's stories -- 1892.